The Social Problem Sensitivity of the Hungarian Population and Their Social Marketing Sensitivity - Piskóti, István (Theory, Methodology, Practice – Review of Business and Management, 2012)
This study moves beyond the institutional approach to social marketing, interpreting social marketing as an integrated model and practice, with the objective of providing more complex solutions to social problems and promoting the achievement of social objectives. The research program, which has been in progress for two years, interprets social marketing as being a form of stakeholder management shaping behaviours acting along value communities. An empirical representative questionnaire inquiry is introduced that assesses sensitivity, undertaking activities and feeling of responsibility of Hungarian citizens towards social problems. This study also analyses the connections between the importance of values, problem-relatedness, individual responsibility, information gathering habits and hindering-factor approaches, that is, Hungarian behavioural elements of integrated social marketing applications.